Evaluation of a smoke-free law on indoor air quality and on workers' health in Portuguese restaurants - Madureira, J. (2015)
Workplace bans on smoking are interventions to reduce exposure to secondhand smoke (SHS) to try to prevent harmful health effects. The Portuguese Government on January 1, 2008, introduced the first national law banning smoking in public workplaces, including restaurants. The main aim of this study was to examine the impact of this law on indoor air quality (IAQ) in restaurants and on the respiratory and sensory health of restaurant workers. Concentrations of respirable suspended particulate matter (RSP), total volatile organic compounds (TVOC), carbon monoxide (CO), and carbon dioxide (CO2) in 10 restaurants were measured and compared before and after the ban. Benzene (C6H6) concentrations were also measured in all restaurants. Fifty-two and twenty-eight restaurant workers, respectively, answered questionnaires on exposure to SHS, and respiratory and sensory symptoms in the pre- and post-ban phases. There was a statistically significant decrease in RSP, CO, TVOC, and C6H6 concentrations after the ban. Additionally, in both phases the monitored CO2 concentrations greatly exceeded 1800 mg x m(-3), suggesting inefficient ventilation of the indoor spaces. Between pre- and post-ban phases a significant reduction in self-reported workplace SHS exposure was also observed after the enforcement of the law, as well as a significant marked reduction in dry, itching, irritated, or watery eyes, nasal problems, sore or dry throat, cough, wheeze, and headache. This study provides, in a single investigation, comparison of IAQ and respiratory health in Portugal before and after the introduction of the smoke-free law, the first data reported in the literature to our knowledge. Our findings suggest that a total workplace smoking ban results in a significant reduction in indoor air pollution and an improvement in the respiratory health of restaurant workers. These observations may have implications for policymakers and legislators currently considering the nature and extent of their smoke-free workplace legislation and could provide a useful contribution to the implementation of public health prevention programs.